Walk & Bike Society in KMUTT THAILAND - Suchada Chaisawadi; Kittinut Kaewthong; Prasert Kanthamanon (Journal of Sustainability Perspectives, 2023)
KMUTT committed to be Green and sustainable university for SDGs 2030 since 2018 and committed to be a part of society that is a major force in promotion and implementation on walk and bike society within the university and expand to communities surrounded. To support walk & bike society in campus, walk & bike master plan has been designed with bike lane, pedestrian cover way, bicycle share services, bicycle repair center and “Zombike” activities which all students and staff make their own bicycle for free by using bicycle accessories from old bicycle in campus. KMUTT Walk & Bike Society policy has been launched since 2018 with bike riding activities which help to support sustainable transportation goal comply to SDG 3: Good Health and Well-being; SDG 7: Affordable and Clean Energy; SDG 11: Sustainable cities and communities and SDG13: Climate Action. The results from 5 years implementation (2018-2022) showed 75% of students and staff walking daily which can make 20,250,000 Km per 5 years in our campus. Bike activities showed daily use and 228 bicycle riding activities in total of 2,008,995 Km distance, initiated by 650 Green heart‘s students and 48,720 people from students, staff and communities participated on these activities. The results showed these walking and riding activities help to reduce carbon emission 3,188 tCO2 and reduce Diesel usage 1.59 million L. KMUTT walk & bike society help to initiate KMUTT sustainable leadership, make Green Heart ‘s students and change agents for helping communities and society expand the sustainable mobility to make healthy and low carbon society, and sustainability for all